2021
DOI: 10.1038/s41418-021-00816-w
|View full text |Cite
|
Sign up to set email alerts
|

BCL-XL is crucial for progression through the adenoma-to-carcinoma sequence of colorectal cancer

Abstract: Evasion of apoptosis is a hallmark of cancer, which is frequently mediated by upregulation of the antiapoptotic BCL-2 family proteins. In colorectal cancer (CRC), previous work has highlighted differential antiapoptotic protein dependencies determined by the stage of the disease. While intestinal stem cells (ISCs) require BCL-2 for adenoma outgrowth and survival during transformation, ISC-specific MCL1 deletion results in disturbed intestinal homeostasis, eventually contributing to tumorigenesis. Colon cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…This finding may have implications regarding the possible use of BCL2 antagonists for the treatment of CRC, and BCL2 mRNA or protein levels as stratification tool for such therapy. Medema et al also demonstrated an enrichment of BCL-2 in immune cells, and a limited window of BCL-2 reliance in CRC cells during disease progression [24]. Their study also demonstrated that expression of BCL(X)L, but not BCL2 or MCL1, correlated with outcome in chemotherapy-treated CRC patients.…”
Section: Discussionmentioning
confidence: 85%
“…This finding may have implications regarding the possible use of BCL2 antagonists for the treatment of CRC, and BCL2 mRNA or protein levels as stratification tool for such therapy. Medema et al also demonstrated an enrichment of BCL-2 in immune cells, and a limited window of BCL-2 reliance in CRC cells during disease progression [24]. Their study also demonstrated that expression of BCL(X)L, but not BCL2 or MCL1, correlated with outcome in chemotherapy-treated CRC patients.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, virus particles can be used for localized recombination when containing the coding sequence for Cre recombinase [ 12 , 31 ]. Additionally, the focal injection of 4-OHT leads to colon tumor formation when a villin Cre ER background is used ( Figure 1 A,B) [ 13 , 15 , 32 ]. In this study, colonoscopy-guided injections could be performed on a benchtop or under a biosafety hood, depending on the specific application and local regulations.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, with local application of 4-OHT, the number of tumors can be controlled and tumor formation is achieved exclusively at the site of injection [ 12 , 13 , 14 ]. The preclinical use of this model was utilized to validate novel therapeutic strategies and demonstrated that BCL-XL inhibition causes impaired adenoma outgrowth [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…S3D) (44), leading to robust increases in apoptosis when ABT-737 was combined with KRAS G12C inhibition in our study. Alongside its pivotal role in regulating MOMP, Bcl-xL has been identified as a critical mediator of stem cell survival through the adeno-to-colon carcinoma sequence (45). Additionally, a number of studies have shown that Bcl-xL plays an important role in regulating sensitivity to chemotherapy and other targeted therapies (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%